THE USE OF THE ROLLING STOCK AUTOMATIC IDENTIFICATION SYSTEM FOR THE PROCESS CONTROL OF THE RAIL INDUSTRIAL ENTERPRISES - Shysh, V. O.; Chykin, Yu. M. (Science and Transport Progress, 2008)
Outlooks of using the rolling stock automatic identification system (RSAIS) on the railway transport in the CIS and Baltic countries, the composition of RSAIS technical means and their positioning on the rail tracks of an industrial enterprise with a purpose of checking the technological processes of operation of the railway facilities are considered. The stages of RSAIS implementation program at an industrial enterprise are discussed.